Differential effects of feedback in the virtual reality environment for arm rehabilitation after stroke - Suradej Tretriluxana (2018)
© 2015 IEEE. Two types of augmented feedback (FB) were compared during reaching training in the Virtual Reality (VR) environment for chronic stroke patients. Six participants were assigned to receive either the Knowledge of Result (KR) or the Knowledge of Performance (KP) FB. They went through 12 training sessions, of which there were 75 Reach-to-Target trials in the VR. They were instructed to perform the actions as fast and accurate as possible. KR group were given audio feedback whereas KP group could see the hand path of their movement. To evaluate, the Wolf Motor Function Test (WMFT) were performed before (Baseline), after (Post training) and 1 week after (Post lweek) the training. Also the kinematics data, Total Movement Time (TMT), Peak Transport Velocity (VMax), and Relative timing of VMax (RP), were analyzed. Results show that only in KP group, the dexterity tasks of WMFT was improved after the training and maintained for at least 1 week. Additionally, VMax in KP group was higher and occurred later than that in KR group. These preliminary outcomes imply that different strategy of movement recovery after stroke result from different types of FB. More participants will be recruited in the future to confirm this finding.